Resonances spectrum of the fiber-coupled microsphere whispering gallery modes and microring resonators for all-optical switching / Ikhwan Naim Md Nawi … [et al.] - Md Nawi, Ikhwan Naim; Ahmad Faizal, Ahmad Fuzairi; Abd Rahman, Mohd Kamil; Ali, Jalil (Institute of Research Management and Innovation (IRMI), 2016)
In recent years, special attentions are paid to the Whispering Gallery Mode (WGM) microresonators and microring resonators (MRR), because they can well confine energy within their structures. WGM and MRR occur at particular resonant wavelengths depending on the size of the resonator. At these particular wavelengths, light undergoes total internal reflection at the surface of the resonator creating resonances in the transmission spectrum of the resonator. In order to couple light in or out of these resonators, the evanescent field of the WGMs has to overlap with the evanescent field of a phase-matched optical bus waveguide. The resonance shift is critically depended on the WGM parameters. This in-and-out coupling of WGM resonators is one of the major technological challenges and can only be achieved by an accurate fabrication. The geometry of the fabricated WGM need to be very smooth an clean to produce sharp spectra. To achieve the resonance, all the WGM and MRR parameters need to be optimized. At the end of the research, we expect to observe an interesting phenomenon that is the resonance peaks in the light intensity spectrum curve is very sharp and the intervals between two successive peaks are very stable. Moreover, the resonance frequencies will shift with the changes of the microsphere size and the optical properties of the surrounding medium. Silicon MRR provides a new platform to form the building block for all-optical switching devices. However, one of the critical problems in achieving a real practical all-optical switching devices is the requirement for a strong material nonlinearity. A strong material nonlinearity is crucial in order to achieve a low switching power. However, siliconbased all-optical switches require extremely high switching power due to its relatively weak nonlinear optical properties. To overcome this limitation, we have designed an all-optical switch configuration based on silicon microring resonator structure and demonstrated the switching operation based on the nonlinear effects induced by a soliton pulse. The soliton pulse induces free-carrier concentration through two-photon absorption (TPA) effect and this leads to enhance the refractive index change and enhance the nonlinearity of the silicon. Thus, the silicon microring resonator alters the nonlinear phase shift which is required for switching. The results demonstrated here will pave the way towards the new on-chip and chip-to-chip architecture and structure for low power and high bandwidth all-optical switch.